VIBRATION CONTROL AND ANALYSIS OF FOUR-PANEL NEEDLE LOOM - MA WeiPing; WANG YanJie; TAO JiuZhi (Jixie qiangdu)
Problems such as strong vibration and low frequency acupuncture exist in four-panel needle loom developed by a Textile Machinery Company. In this paper, the vibration test and analysis of the whole needle loom are carried out to find out the causes of vibration.Through the kinematics and dynamics analysis of the motion mechanism of the needle loom, the exciting force is calculated and the solution is given.Through vibration test and dynamic balance testing, vibration and noise caused by machining and assembly errors are eliminated.Finally, it provides an effective solution to the problem that the vibration of the four-plate high speed needle loom is too large and the needling frequency is too low.